International education: career paths in science and engineering - Calvert, Gregory (Curtin University, 2006)
This study examines the relationship between international fee-paying students and career pathways through courses of study in Science and Engineering. International education is a significant endeavour in Australia in terms of any measure (students, dollars, associated employment). Over the last two decades it has grown in scope, beyond international fee-paying students, so that it now crosses all sectors of education and training (schools, vocational education and training, and higher education). Australian institutions have expanded their enrolment offshore and engaged in a variety of joint venture activities to capitalise on this surge of interest. The study examined international fee-paying students and career pathways shortly after the Organisation of Economic Co-operation and Development (OECD) conducted two major studies in 2004 into career education and transnational education amongst member countries. The links between course and career intentions were investigated by focusing on the subject fields of Science and Engineering. The term career pathway is used as a metaphor to describe the way students move through the Australian education and training system, with such movements possibly occurring through sequential levels or by sectors. A literature review was conducted initially, and a mixed research methodology (involving both quantitative and qualitative approaches) was adopted for the study. A survey instrument was used with a sample of 110 international fee-paying students drawn from students studying Science and/or Engineering at nine institutions across sectors of Australian education and training, then a further sample of 22 students was interviewed in order to gain an understanding of the underlying reasons for students making the decisions, in relation to courses and careers that they do.These samples provide the opportunity to evaluate international students' understandings of the Australian education and training system, especially the entry procedures into Science and/or Engineering courses. As part of the methodology the preliminary results were shared with the institutions involved to gain their input. Major findings were that 68 percent of the sample did not have career preparation or advice before coming to Australia; 52 percent of the sample was able to explain the term 'credit-transfer'; 53 percent of the sample had researched the recognition of their course in their home country, and careers advice was sought by 58 percent of the sample whilst studying in Australia. Resulting from the study are a number of recommendations for major stakeholders associated with international education (Australian Educational International, the Graduate Careers Council of Australia, government policy makers, institutions, the related professional bodies in the fields of Science and Engineering, and international fee-paying students). The findings of this study have implications for the way in which careers services are provided to international fee-paying students at Australian institutions. The outcome of this study is presented in two volumes. Volume One contains the body of the thesis in 6 Chapters. Volume Two (on disk) includes the associated documents of this study, presented in twelve Appendices.